Caracterização de níquel eletrodepositado em substrato de cobre - Erik Luis Sardinha Cecconello (2006)
Tribological properties of engineering materials are enhanced with the use of coatings. In the steel industry, nickel coatings on copper have increased the useful life of continuous ingot casting molds. The electrodeposited nickel increased the resistance to friction andabrasive wear between the steel and the copper used in the molds. The objective of this work was to study the morphology and to determine the porosity of nickel electrodeposited on copper by using a bath of nickel sulfamate. The morphology evaluation was done using the scanning electron microscopy. The effective porosity in nickel coatings was determined by using the anodic voltammetry. This technique consists in comparing the charge density involved in the passivation process of the substrate without a nickel coating and that required to the passivation of the substrate covered with a nickel layer.